The rise of Aurora West - Petty, J. T. (John T.); Pope, Paul (First Second, 2014)
In the city of Arcopolis, where monsters run wild, Aurora West is busy with martial arts lessons, school, and helping her hero father on his missions. As she embarks on her own quest to become a hero, she begins to unravel the mystery surrounding her mother's death.